A single case-study of the use and understanding of learning technology within a university faculty of humanities: a critical theory approach - Kathryn, James (2018)
Learning technologies are endorsed though government and university agendas through a discourse of educational transformation. These enhancements are promoted as universal and equal across disciplines with a focus on the delivery of educational efficiencies, flexibility, and employment skills. From the position of academic developer with a remit for the promotion of learning technology, this thesis questions the technical universalism that portrays equivalence of need and benefit of learning technology in higher education regardless of discipline or institutional context. Supported by Habermas’s (1984 and 1987) theories of communicative action, lifeworld and colonisation thesis, the study explores the lifeworld and teaching practice of academics in a single faculty of humanities, and considers the impact of their using learning technologies. It addresses the questions: What learning technologies did the academics in a faculty of humanities within the University use and why; and, what were the institutional drivers for this use? The research adopts a single case-study methodology. The case was academics in a university faculty of humanities and it explored the issue of learning technology use. Data was generated from 26 semi-structured interviews with academics across a range of humanities disciplines within one university faculty, and from an analysis of the University Learning and Teaching Strategy (L&TS). Interviews were coded utilising template analysis, supporting categorisation of priory themes aligned to the broad research questions. The research found academics in the humanities faculty used pedagogic practices centred on communicatively structured activities, which emphasise student engagement in discussion, reflection and reasoned argument aimed towards developing critical thinking skills. These practices mirror humanities academics’ own ontology and epistemologies, which consider education as a route towards personal development, and which recognise the important of human values, responsibility, and empathy. Taken as a whole, the findings show that the humanities academics were thoughtful and pragmatic in their engagement with technology for teaching. They acknowledged learning technology’s importance and benefits but were, however, ambivalent about its value for enhancing pedagogic practice and learning. Furthermore, the data showed that when driven by instrumental rationality and strategic actions that preferences an economic model for higher education above one of human development, learning technology had subtle, unintended, and contentious impacts. These impacts manifested themselves in a range of tangible symptoms, that Habermas terms ‘pathologies’. These included a culture of surveillance and mistrust, individual anxiety, and negative self-efficacy. Academic development scholarship recognises the importance of working alongside and within discipline communities to support pedagogic practice. The learning technology discourses and its implementation takes a more generic position. This study argues that before an academic developer promotes the use of a particular learning technology in an attempt to improve pedagogic practice, they must not only have a thorough knowledge of successful implementations of learning technology, but also an understanding of the academic lifeworld, and teaching philosophies of the discipline. This knowledge can support a process of communicative action whereby mutual understanding and agreement can lead to shared value, and action orientated towards a better understanding of learning technology’s discipline appropriateness for teaching purposes.